Efficacy of integrated traditional Chinese medicine and Western medicine in the treatment of poststroke insomnia: A protocol for systematic review and meta-analysis of randomized controlled trials - Li, Wenwen; Liu, Cuncheng; Wang, Ruiqi; Liu, Ruxue; Peng, Min; Si, Guomin (Medicine (Baltimore), 2021)
Western medicine has played an essential role in treating poststroke insomnia (PSI) in China, and traditional Chinese medicine therapy based on Chinese characteristics is also effective. Combined with China's national conditions, we plan to conduct this systematic review and meta-analysis to compare the efficacy of integrated traditional Chinese medicine and Western medicine (INTEGRATED TCM and WM) therapy and Western medicine alone for PSI. We will search the following 5 electronic databases: PubMed, Wanfang, Chinese biomedical literature database, the Chongqing VIP Chinese Science and Technology Periodical, and China national knowledge infrastructure. Randomized controlled trials that compared the efficacy of INTEGRATED TCM and WM with Western medicine alone in the treatment of PSI will be considered. Primary outcomes have Treatment effectiveness rate, and Pittsburgh sleep quality index. Secondary outcomes include traditional Chinese medicine syndrome score, Athens insomnia scale, the incidence of adverse reactions, and outcome follow-up. Based on the eligibility criteria, we will conduct literature screening and data extraction. The quality of the included literature will be evaluated using the Cochrane risk of bias tools. We will use Review Manager software (Version 5.3) for data synthesis and statistical analyses. If sources of heterogeneity exist, we will perform a subgroup analysis or sensitivity analysis. A funnel plot will be used to analyze publication bias. This study will provide evidence-based medicine evidence for treatment of PSI with INTEGRATED TCM and WM in terms of its efficacy. This systematic review aims to provide new options for INTEGRATED TCM and WM treatment of PSI in terms of its efficacy.